Social Psychology / HarperCollins College Outline - Harperperennial; Weber Ann L (1992)
This book is part of an all-new, in depth series, featuring titles in all areas of study, including Humanities, Social Science, Business, Engineering, Science, Mathematics, and Computer Science. Preface, Introduction to Social Psychology, Social Psychological Research, Social Cognition, The Social Self, Person Perception, Attribution, Gender and Social Behavior, Attitudes and Behavior, Changing Attitudes, Social Influence, Group Behavior, Prejudice and Discrimination, Aggression, Conflict, Interpersonal Attraction, Close Relationships, Prosocial Behavior, The Environment and Behavior, Social Psychology and Health, Social Psychology and the Legal System, Glossary, Index.